Analysis of Thermal Conditions in a Simple Grain Dryer Building - Alahudin, Muchlis; Topan, Anton; Simorangkir, Yosi Valentina (Engineering And Technology Journal, 2023)
Drying buildings are really needed by farmers during the harvest season, the drying buildings that Merauke farmers often use are natural drying buildings whose heat source comes from the sun. The use of dryer buildings is considered more efficient when drying, this is because the farmers in Merauke have quite a hard time when the harvest arrives, when the harvest arrives the rainfall is still high. The purpose of this study was to determine the thermal conditions in a simple dryer building. This research type is experimental research. Temperature measurements were carried out for 1 week from 1 October 2022 – 6 October 2022. The results showed that inside the grain drying buildings the average temperature reached 34.2°C and the average humidity reached 73.9%. Meanwhile outside the building the average temperature reaches 31.8°C and the average humidity reaches 81%. During the measurement period, the highest temperature inside the building reached 43.4°C, causing the grain which was dried in the sun to dry quickly.